2010
DOI: 10.1208/s12248-010-9178-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cannabinoids in the Development of Fatty Liver (Steatosis)

Abstract: Abstract. Emerging evidence suggests that cannabinoids play an important role in the modulation of fatty liver, which appears to be mediated via activation of cannabinoid receptors. Steatogenic agents such as ethanol and high-fat diet can upregulate the activity of cannabinoid 1 (CB1) receptors via increasing synthesis of endocannabinoids, 2-arachidonoylglycerol, and anandamide. CB1 receptors can also be upregulated by obesity. CB1 receptor activation results in upregulation of lipogenic transcription factor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 25 publications
2
77
3
Order By: Relevance
“…However, in this study, the effects of the accumulation of lipid in the hepatocytes of individuals from treated groups led to cytoplasm disorganization, which caused structural and physiological alterations in the organ, once in the cellular metabolism all the enzymatic synthesis activity seems to have been concentrated on the attempt to produce enzymes to metabolize the molecules of fipronil to eliminate them from the system. Purohit et al 2010 found similar results studying the receptors of cannabinoids (cannabinoid 1 receptor-CB1; e cannabinoid 2 receptor-CB2) and the relation between these receptors and the agents, which are considered factors in the steatosis etiopathogenesis, such as ethanol and high-fat diet. These authors observed that, once these agents activate CB1, there would be an increase in the synthesis of fatty acids and a decrease in their oxidation, resulting in an accumulation of lipid in the liver.…”
supporting
confidence: 59%
“…However, in this study, the effects of the accumulation of lipid in the hepatocytes of individuals from treated groups led to cytoplasm disorganization, which caused structural and physiological alterations in the organ, once in the cellular metabolism all the enzymatic synthesis activity seems to have been concentrated on the attempt to produce enzymes to metabolize the molecules of fipronil to eliminate them from the system. Purohit et al 2010 found similar results studying the receptors of cannabinoids (cannabinoid 1 receptor-CB1; e cannabinoid 2 receptor-CB2) and the relation between these receptors and the agents, which are considered factors in the steatosis etiopathogenesis, such as ethanol and high-fat diet. These authors observed that, once these agents activate CB1, there would be an increase in the synthesis of fatty acids and a decrease in their oxidation, resulting in an accumulation of lipid in the liver.…”
supporting
confidence: 59%
“…Cannabinoid-1 receptor (CB1), which responds to cannabinoids that increase fat intake, regulates the activity of these lipogenic and lipolytic transcription factors [6, 7], and the intake of ethanol and high-fat diet induce upregulation of CB1 activity through increased synthesis of endocannabinoids, 2-AG, and anandamide [1]. Because CB1 is also upregulated in obesity, CB1 is a potential therapeutic target for obesity and NAFLD [8].…”
Section: Introductionmentioning
confidence: 99%
“…-THC treatment promote steatosis and are associated with development of NAFLD (14,15). Similarly, activation of the endogenous EC system to increase AEA, 2-AG, and CB1 is linked to NAFLD (8)(9)(10).…”
mentioning
confidence: 99%
“…The mechanism whereby CB1 induces hepatic lipid accumulation involves downstream upregulation of sterol regulatory element binding protein 1c (SREBP1c) which in turn induces transcription of de novo lipogenic enzymes (8,14). However, it is not known if Δ…”
mentioning
confidence: 99%